PENGARUH KEPEMIMPINAN ETIS DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI PADA BALAI BESAR WILAYAH SUNGAI BENGAWAN SOLO - Salsabilla, Deandra Nurul Izza Alfia; Mardalis, Ahmad (JURNAL LENTERA BISNIS, 2026)
This research is designed to examine the effects of ethical leadership and compensation on employee performance, with work motivation functioning as a mediating construct at the Bengawan Solo River Basin Center. Employing a quantitative methodology, the study targeted all employees as the population, while the sample size determined using the Lemeshow formulaadapun dyielded a minimum requirement of 97 participants. Primary data in this study were collected using a Likert-scale questionnaire that measured ethical leadership, compensation, motivation, and employee performance. In contrast, the secondary data were obtained from organizational documents and internal administrative records. The analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the support of the SmartPLS application. The results revealed that both ethical leadership and compensation have a positive and statistically significant impact on employee performance. These two variables were also shown to significantly improve employees’ work motivation. Furthermore, work motivation itself was positively and significantly associated with employee performance. The analysis also confirmed that motivation serves as a partial mediator in the link between ethical leadership and employee performance, as well as between compensation and employee performance. Overall, the findings suggest that improving employee performance can be effectively achieved by promoting ethical leadership, ensuring adequate compensation, and fostering higher levels of work motivation.